The role of social networks in production of the migrant’s identity - M. A. Panarina; I. A. Lavrov (Цифровая социология)
The process of migration is widespread and captures millions of people each year. The identity of those with migration experience is reconstructed by different culture of the receiving country and specific multicultural diverse space. The experience of studying this problem by foreign sociologists and  anthropologists of different years has been considered in the article. The dynamics of the development of approaches to the study of this multifaceted and complex issue is monitored. The basic human identity formation concepts in the context of migration have been presented and analyzed, among which are: structuralism, the concept of transnational migration, the multicultural theory, the concepts of diversity and super-diversity. Based on the advantages of each of the concepts and taking into account their shortcomings, the main formation factors of personal identity, the role and importance of each of these factors in modern conditions of migration have been formulated.The main thesis is that social networks leading to the accumulation of social capital, play the major role in this process, providing the structure for exchanging the ideas, values and identities over geographical and administrative obstacles. These social networks are highly dynamic and have different influence on the migrants’ identity and, consequently, have a significant impact on the prospects for their adaptation in a new country. People with migrant background become competent navigators within the super-diversity environment.Migration processes remain extremely complex due to their dynamic and ambivalent nature, but their study is a crucial task for the modern and open world, as a person moves not only physically from country to country, but also brings his own cultural samples, which in cooperation with the cultural samples of the receiving country, form a new reality.